2022
DOI: 10.1371/journal.pone.0271628
|View full text |Cite
|
Sign up to set email alerts
|

Age impacts left atrial functional remodeling in athletes

Abstract: Aim Age-associated changes in cardiac filling and function are well known in the general population. Yet, the effect of aging on left atrial (LA) function, and its interaction with left ventricular (LV) adaptation, remain less described when combined with high-intensity chronic training. We aimed to analyze the effects of aging on LA and LV functions in trained athletes. Methods and results Ninety-five healthy highly-trained athletes referred for resting echocardiography were included. Two groups of athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Cousergue et al demonstrated a strong relationship between age-induced changes in LV diastolic function and left atrial (LA) function in healthy young (<35 years) and master (>35 years) athletes using echocardiography [ 20 ]. Importantly, Torlasco et al found key differences in the pattern of adaptation caused by physical activity using CMR.…”
Section: Normal Ranges For Healthy Cardiac Adaptation—what Do I Mean ...mentioning
confidence: 99%
“…Cousergue et al demonstrated a strong relationship between age-induced changes in LV diastolic function and left atrial (LA) function in healthy young (<35 years) and master (>35 years) athletes using echocardiography [ 20 ]. Importantly, Torlasco et al found key differences in the pattern of adaptation caused by physical activity using CMR.…”
Section: Normal Ranges For Healthy Cardiac Adaptation—what Do I Mean ...mentioning
confidence: 99%